2017
DOI: 10.1371/journal.pntd.0005596
|View full text |Cite
|
Sign up to set email alerts
|

Migratory phase of Litomosoides sigmodontis filarial infective larvae is associated with pathology and transient increase of S100A9 expressing neutrophils in the lung

Abstract: Filarial infections are tropical diseases caused by nematodes of the Onchocercidae family such as Mansonella perstans. The infective larvae (L3) are transmitted into the skin of vertebrate hosts by blood-feeding vectors. Many filarial species settle in the serous cavities including M. perstans in humans and L. sigmodontis, a well-established model of filariasis in mice. L. sigmodontis L3 migrate to the pleural cavity where they moult into L4 around day 9 and into male and female adult worms around day 30. Litt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(60 citation statements)
references
References 57 publications
4
56
0
Order By: Relevance
“…The transcriptomic profiling of the pulmonary neutrophils after helminth infection was shown to be distinct from the transcriptional profile to those activated by lipopolysaccharide, with the upregulation of genes involved in collagen production, ECM pathways and chitin metabolism. Studies in the field of cancer research also support the idea that neutrophils can polarize into N1 or N2 subset, akin to M1 or M2 macrophage . The idea that heterogeneity among neutrophils exists is apparent by their morphological differences (including nuclear appearance and cell density) and surface receptor expression.…”
Section: Neutrophil–macrophage Cooperation During Tissue Repairmentioning
confidence: 86%
See 1 more Smart Citation
“…The transcriptomic profiling of the pulmonary neutrophils after helminth infection was shown to be distinct from the transcriptional profile to those activated by lipopolysaccharide, with the upregulation of genes involved in collagen production, ECM pathways and chitin metabolism. Studies in the field of cancer research also support the idea that neutrophils can polarize into N1 or N2 subset, akin to M1 or M2 macrophage . The idea that heterogeneity among neutrophils exists is apparent by their morphological differences (including nuclear appearance and cell density) and surface receptor expression.…”
Section: Neutrophil–macrophage Cooperation During Tissue Repairmentioning
confidence: 86%
“…Studies in the field of cancer research also support the idea that neutrophils can polarize into N1 or N2 subset, akin to M1 or M2 macrophage. 61,62 The idea that heterogeneity among neutrophils exists is apparent by their morphological differences (including nuclear appearance and cell density) and surface receptor expression. Whether this heterogeneity simply reflects different maturation states-or whether it correlates with the polarization of neutrophils into N1 and N2 subtypes is unclear.…”
Section: Neutrophil Plasticitymentioning
confidence: 99%
“…Recently, it was demonstrated that L. sigmodontis L3 larvae trigger the expression of S100A9 in neutrophils during their migration through the lung into the thoracic cavity [38]. In the present study we investigated the impact of calprotectin during L. sigmodontis infection in C57BL/6 mice lacking S100A9 and compared the worm burden and immune responses to C57BL/6 WT controls.…”
Section: Introductionmentioning
confidence: 95%
“…Mice were exposed simultaneously to the same batch of O. bacoti mites to ensure a comparable infection of both groups [47]. For subcutaneous or intravenous infections of mice, L3 larvae were isolated from mites [38] or 5 day-infected gerbils (Meriones unguiculatus) [55] and 40 L3 larvae were subcutaneously injected into the neck region or inguinal regions or intravenously into the caudal vein. Necropsy was performed on day 12 after L. sigmodontis infection using an overdose of Isoflurane (Forene) and worms were isolated from the thoracic cavity by lavage and quantified using a binocular microscope.…”
Section: Mice and Infectionmentioning
confidence: 99%
See 1 more Smart Citation